Implementasi Fitur-Fitur Interaksi Pengguna Pada Permainan Simulasi Ujian Berkendara 3D - Indriadi Setiawan; Eriq Muh. Adams Jonemaro; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Driving simulation game is one type of simulation game that enables players to pilot or drive a vehicle, and focus on creating the real experience as possible. Oculus itself is used as a replacement wearable device monitor in playing games to get the sensation of playing real on the Virtual world. Human computer interaction is a relationship between humans and computers that have certain characteristics to achieve certain goals by running a system that masks an interface. Testing are using usability to measure user satisfication from sistem that created. The result of usability testing with satisfication criteria shows that 74% of all respondents are satisfied with the system built.